Pemeriksaan Pertumbuhan Janin - Laksmi Maharani; Denny Dhanardono; Irmiya Rachmiyani; Imelda Yunitra (CV. Multi Kreasi Media, 2023)
Antenatal care is a crucial activity that should be done periodically in all pregnant women. The goal of antenatal care is to monitor the growth and development of the fetus and to prepare the women to successfully deliver healthy baby. Monitoring fetal growth is important to detect fetal growth restriction condition promptly and make any intervention needed as soon as possible to avoid further complications. The measurement can be done conventionally by measuring the fundal height. On the other hand, ultrasound scanning to measure fetal biometry is more accurate to do so. A community serviced activity has been performed to monitor fetal growth at Kelurahan Ciangsana to 24 pregnant women, which showed a quite good result.